Attitudes of Some African Youth toward Sex and Marriage - Trobisch, Walter (Practical anthropology, 1962)
In this article the author analyzes the results of an informal survey of the attitudes of his students toward premarital sex relations and marriage. The article is written in the light of two previous articles in Practical Anthropology.1 Trobisch discusses the need for an African Christian theology of marriage, and for relevant teaching in the light of African assumptions and presuppositions as revealed in this small sample and through his other observations.